2020
DOI: 10.3390/ijms21176106
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Functionality Study of 9 Toll-Like Receptors in 33 Drug-Naïve Non-Affective First Episode Psychosis Individuals: A 3-Month Study

Abstract: Toll-like receptors (TLRs) are a pivotal component of the innate immune system that seem to have a role in the pathogenesis of psychosis. The purpose of this work was to compare the expression and functionality of 9 TLRs in three peripheral blood mononuclear cells (PBMCs) (monocytes, B cells, and T cells) between 33 drug-naïve first-episode psychosis (FEP) individuals and 26 healthy volunteers, at baseline and after 3-month of antipsychotic treatment. The expression of TLRs 1–9 were assessed by flow cytometry.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…There is evidence that TLR1, TLR2, TLR4, TLR6, and TLR9 expression levels in peripheral blood mononuclear cells (PBMCs) are reduced in schizophrenia, TLR3 and TLR7 levels are elevated, and TLR5 and TLR8 levels do not differ from controls ( 24 ). In another study, TLR5 and TLR8 expression levels in PBMCs decreased in drug-naïve first-episode psychosis individuals before and after treatment compared to controls ( 25 ). A lower functional activity of TLRs after agonist activation has also been shown.…”
Section: Alterations In the Innate Immune System In Schizophreniamentioning
confidence: 99%
“…There is evidence that TLR1, TLR2, TLR4, TLR6, and TLR9 expression levels in peripheral blood mononuclear cells (PBMCs) are reduced in schizophrenia, TLR3 and TLR7 levels are elevated, and TLR5 and TLR8 levels do not differ from controls ( 24 ). In another study, TLR5 and TLR8 expression levels in PBMCs decreased in drug-naïve first-episode psychosis individuals before and after treatment compared to controls ( 25 ). A lower functional activity of TLRs after agonist activation has also been shown.…”
Section: Alterations In the Innate Immune System In Schizophreniamentioning
confidence: 99%
“…TLRs often presented a reduced functionality (in particular decreased intracellular concentrations of TNF‐α) in patients compared to healthy subjects. Together, these findings indicate that individuals with psychosis could present with a pattern of TLR production that is distinct from that of healthy subjects, that could fluctuate based on the severity of immunological feedback 272 …”
Section: Role Of Tlrs In Neuropsychiatric Disordersmentioning
confidence: 86%
“…270 A study compared the production that is distinct from that of healthy subjects, that could fluctuate based on the severity of immunological feedback. 272…”
Section: Clinical Trialsmentioning
confidence: 99%
“…[ 60 ]. Multiple studies show altered protein and mRNA expression of TLRs in schizophrenia ( Table 1 ) compared to healthy adults [ 61 , 62 , 63 ]. Human postmortem studies carried out on individuals diagnosed with schizophrenia, brain samples showed lower tlr4 mRNA and protein levels, and downregulation of il6 , il10 , and tnfa mRNA in the prefrontal cortex (PFC) region [ 64 , 65 ], and elevated TLR4 protein levels in the cerebellum region [ 64 ].…”
Section: The Role Of Toll-like Receptors In Schizophreniamentioning
confidence: 99%
“…In contrast, whole blood stimulation studies in schizophrenia showed elevated concentrations of IL-6, TNF-α, and IL-1β post-TLR2 stimulation, and increased IL-1β alone post-TLR4 and 8 stimulation [ 7 ]. Individual blood cell studies in FEP patients showed lower TLR protein expression in monocytes, B cells, and T cells [ 63 ]. Overall, we can infer that dysregulation of TLR expression exists in patients with schizophrenia and varies at various stages of disease progression, but we do not have sufficient evidence to implicate their extent of involvement in the immunopathology of schizophrenia.…”
Section: The Role Of Toll-like Receptors In Schizophreniamentioning
confidence: 99%